Quantification of historical exposures in occupational cohort studies - Stewart, Patricia A.; Lees, Peter SJ; Francis, M. (Scandinavian Journal of Work, Environment & Health, 1996)
Relatively few investigators have estimated quantitative exposure levels in epidemiologic studies, and, for those that have, few have discussed the strengths and weaknesses of their estimation method with respect to other methods. This paper reviews the steps for developing quantitative exposure estimates that have been used in published studies. First, the qualitative considerations to be evaluated in the selection of the agent to be estimated (ie, the disease mechanism, the effects of exposure mixtures and interactions, the physical state of the agent, and the routes of exposures) are discussed. Considerations for developing exposure groups are then presented, including work history and exposure information characteristics, the homogeneity of exposures within exposure groups, the exposure estimation method, and the disease risk analyses to be performed. The various exposure estimation approaches are reviewed for their strengths and weaknesses, including the calculation of the mean exposures from existing exposure measurements, statistical models, measurement data from surrogate exposures, and professional judgment. Recommendations for future studies are provided.
Keywords: cohort study; epidemiologic study; exposure assessment